Dagestan Modern Russian-Language Poetry at the Crossroads of Cultures - Akamov, Abusupyan T.; Alibekova, Patimat M.; Bedirkhanov, Seyfeddin A.; Gadzilova, Shanisat M.; Magomedova, Zuleikhat K. (Journal of History Culture and Art Research, 2018)
Russian-language literature is an objective phenomenon of the literary process, a typological, natural phenomenon, conditioned by the historical and cultural context of time. In this regard, literary Russian-language becomes a topical theoretical and literary study problem, the tradition of special study and scientific reflection. In this article, the authors studied the processes of a new literary community development based on integration experience, which has been an important factor in the development and the enrichment of Dagestan poetry for centuries. The twentieth century has become the century of conjugation for cultures. The principle of a dialogue between cultures determines the understanding of Russian-language poetry as a borderline phenomenon, whose originality is conditioned by a close interaction and a mutual influence of national cultures with Russian and foreign poetic traditions. The article reveals the causal relationship of some artistic trends in a temporal context. Arabic, Persian, Turkic, and then Russian influence formed an aesthetic system, differing by the variety of artistic expression forms. Classical Iranian stories, Sufi symbols, Russian poetry of the Silver Age were reflected here. A notable phenomenon of modern Russian-language poetry was represented by the appeal of the Dagestani authors to the East, now often through Russian and European literature. The echoes of Eastern classical poetry are revealed, which enriched the poetry of Byron, Goethe, Heine, Pushkin and which have a direct connection with the process of modern, Russian-speaking Dagestani poetry development, the influence on the definition of its directions with their inner content, pathos and pathetic. In this article a particular attention is paid to such a form of cultural, spiritual, ethical-aesthetic exchange as translation.